Avaliação da autoestima, do consumo de álcool, de tabaco e de outras substâncias em trabalhadores terceirizados de uma universidade pública - Nadaleti, Nayara Pires (2018)
Outsourcing has increasingly become a common procedure among companies in Brazil as well as all over the world. It usually depicts a set where outsourcing workers may assume low-skilled and low-valued occupations which mainly consist of manual labor, requiring physical effort. This kind of service can be poor and have consequences for welfare and health of its workers. Among such consequences, changes in self-esteem and consumption of substances, including alcohol and tobacco, are highlighted. Thus, this study aims at assessing the self-esteem as well as the alcohol, tobacco and other substances consumption among outsourcing workers from a public university in a city in the south of Minas Gerais. It is a qualitative, descriptive analytical and cross-sectional study, performed with 316 outsourcing workers from a public university from the city of Alfenas-MG. Data collection was conducted between December 2016 and February 2017, and it used the following instruments: Instrument of characterization, Alcohol, Smoking and Substance Involvement Screening Test e Fagerström Test for Nicotine Dependence. The level of carbon monoxide in exhaled air was also evaluated through the monoximeter. In order to analyze data, it was used: descriptive statistics, Cronbach's alpha coefficient, Pearson's chi-square test and Fisher's exact test with significance level set at 5%. The odds ratio were estimate with a confidence interval of 95%, as well as the logistic regression. As a result, it could be found that most of the outsourcing workers were females; aged from 30 to 39; married or living with partners; catholic; with kids; house hold incomes from R$ 1.501 to R$ 3.000 . Most of the workers were secretaries who have worked for outsourcing for up to 10 years, and for the institution 4 years or more. Most of those workers had high self-esteem; the most present substances during their lives were alcohol, tobacco, marijuana and inhalants; and great part of them showed as either low physically dependent on tobacco or smoker. It could be concluded that only the sex, age and working shift in the institution had statistical association to the levels of self-esteem; that the variables which had statistical association to the risks from developing complications around alcohol consumption were sex, age, marital status, religious belief and number of kids; and finally that only the variable of practicing physical exercises showed statistical association to risks of developing complications from consuming tobacco-derived products. There was no statistical association between the risk of developing complications from consuming alcohol or tobacco-derived products and the levels of self-esteem. Physical dependence on tobacco showed statistical association to the smoker status. Therefore, it might be noticed how much outsourcing companies need to provide better work conditions to their employees as well as help in favor of improving their work and social quality of life. Besides the companies should adopt measures that hold motivating factors of mental illnesses, changes in self-esteem and consumption of substances.